2013
DOI: 10.1111/liv.12022
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to soluble liver antigen in patients with various liver diseases: A multicentre study

Abstract: Seropositivity for anti-SLA occurs at similar frequencies in AIH patients from different geographical regions and ethnic groups. The sensitivity of anti-SLA is low, but it has high specificity for AIH. Additional studies are necessary to prove clinical significance of anti-SLA in AIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 44 publications
1
42
0
5
Order By: Relevance
“…Anti-SLA was described in patients running a severe clinical course, having worse histology, needing a longer period to achieve remission, relapsing and requiring liver transplantation more frequently [9] . These clinical correlations, obtained with an extremely sensitive immunoassay able to identify antibodies directed to conformational epitopes, were partially replicated in a large series of patients [23] , but not in other studies [24,25] , and such a difference might be due to the different methods employed for anti-SLA detection.…”
Section: Autoantibodies Of Diagnostic Relevancementioning
confidence: 83%
“…Anti-SLA was described in patients running a severe clinical course, having worse histology, needing a longer period to achieve remission, relapsing and requiring liver transplantation more frequently [9] . These clinical correlations, obtained with an extremely sensitive immunoassay able to identify antibodies directed to conformational epitopes, were partially replicated in a large series of patients [23] , but not in other studies [24,25] , and such a difference might be due to the different methods employed for anti-SLA detection.…”
Section: Autoantibodies Of Diagnostic Relevancementioning
confidence: 83%
“…Of these, 15 (51.7%) studies were in English [45][59] and 14 (48.3%) were in Chinese [60]–[73]. Eighteen studies on 968 patients investigated the diagnostic accuracy of ANA [45]–[47], [50], [52], [54], [59]–[62], [64]–[68], [70], [71], [73], 22 studies on 1,193 patients reported on the diagnostic accuracy of SMA [46], [47], [50], [52][55], [57][59], [60]–[65], [67]–[71], [73], and 16 studies on 850 patients focused on the diagnostic accuracy of anti-SLA/LP [46][52], [56], [60], [63], [65], [68]–[70], [72], [73].…”
Section: Resultsmentioning
confidence: 99%
“…Lactation without pregnancy could be explained by hyperprolactinemia. Associations of AIH with primary biliary cirrhosis and primary sclerosing cholangitis have been described [2] . Association of AIH with organ specific polyglandular autoimmune disease have also been found due to defect in autoimmune regulatory gene (AIRE) but no association with microadenoma of pituitary and hyperprolactinemia have been described [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Anti SLA have high specificity for AIH because 90% cases anti SLA positive patients have AIH & only 10% have primary biliary cirrhosis. Biochemical remission is achieved in 90% anti SLA positive AIH but relapse is seen in 53% patients after withdrawal of immunosuppressive drugs [2] . Anti SLA antibody positive patient are mostly DRB1*03 positive and have anti SSA (R0-52) antibody, ANA and ASMA [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation